Military force mobility as a challenge for the European Union in the field of defence - Stanić, Vladan (Napredak, 2025)
The paper analyzes the triggers for the consideration and the extent to which the European Union has improved military force mobility in Europe. Military force mobility ensures efficient, timely and safe transport and deployment of military staff, weapons and equipment for the needs of conducting missions, operations, exercises or everyday activities. The Russian-Ukrainian conflict pointed to an urgent need of substantially improving military force mobility within and outside the European Union through the realization of projects related to military mobility and through the development of the dual-purpose transport infrastructure within the trans-European transport network. Free movement of military forces in Europe, without any obstacles, is the question of strategic importance both for the EU and the NATO. However, it has been concluded that the current state of traffic communications is not at the satisfactory level and, according, the EU (and the NATO) undertake comprehensive measures to create conditions for completely unobstructed movement of their own military forces. The conclusions in this paper have been drawn mainly by the use of the analysis method and the comparative method. The data were collected by the qualitative content analysis of the relevant documents and statements, while the presentation is mostly chronological. In disciplinary terms, the paper is founded on science of international relations, chiefly on the foreign policy analysis.